Amphipathic Side Chain of a Conjugated Polymer Optimizes Dopant Location toward Efficient N‐Type Organic Thermoelectrics. Issue 4 (11th December 2020) - Liu, Jian; Ye, Gang; Potgieser, Hinderikus G. O.; Koopmans, Marten; Sami, Selim; Nugraha, Mohamad Insan; Villalva, Diego Rosas; Sun, Hengda; Dong, Jingjin; Yang, Xuwen; Qiu, Xinkai; Yao, Chen; et al.
Abstract: There is no molecular strategy for selectively increasing the Seebeck coefficient without reducing the electrical conductivity for organic thermoelectrics. Here, it is reported that the use of amphipathic side chains in an n‐type donor–acceptor copolymer can selectively increase the Seebeck coefficient and thus increase the power factor by a factor of ≈5. The amphipathic side chain contains an alkyl chain segment as a spacer between the polymer backbone and an ethylene glycol type chain segment. The use of this alkyl spacer does not only reduce the energetic disorder in the conjugated polymer film but can also properly control the dopant sites away from the backbone, which minimizes the adverse influence of counterions. As confirmed by kinetic Monte Carlo simulations with the host–dopant distance as the only variable, a reduced Coulombic interaction resulting from a larger host–dopant distance contributes to a higher Seebeck coefficient for a given electrical conductivity. Finally, an optimized power factor of 18 µW m –1 K –2 is achieved in the doped polymer film. This work provides a facile molecular strategy for selectively improving the Seebeck coefficient and opens up a new route for optimizing the dopant location toward realizing better n‐type polymeric thermoelectrics. Abstract : Selective increase in the Seebeck coefficient and improvement of the power factor by a factor of ≈5 in an n‐doped donor–acceptor copolymer are realized by the use of amphipathic side chains. This strategy can properly control the dopant sites away from the backbone, which minimizes the adverse influence of counterions. Therefore, an excellent power factor of 18 µW m –1 K –2 is achieved.